2013
DOI: 10.1186/1479-5876-11-119
|View full text |Cite
|
Sign up to set email alerts
|

Use of V(D)J recombination excision circles to identify T- and B-cell defects and to monitor the treatment in primary and acquired immunodeficiencies

Abstract: T-cell receptor excision circles (TRECs) and kappa-deleting recombination excision circles (KRECs) are circular DNA segments generated in T and B cells during their maturation in the thymus and bone marrow. These circularized DNA elements persist in the cells, are unable to replicate, and are diluted as a result of cell division, thus are considered markers of new lymphocyte output. The quantification of TRECs and KRECs, which can be reliably performed using singleplex or duplex real-time quantitative PCR, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 100 publications
3
62
0
7
Order By: Relevance
“…Thus, the results obtained from the TREC assay may be used to classify patients based on the status of their immunity, predicting susceptibility to infections. In this study, we found that the TREC levels were significantly lower in individuals with 22q11.2DS compared with healthy controls and tended to decrease with age due to the natural thymic involution, as has been previously shown (6,(22)(23)(24). Furthermore, lower TREC levels were found in 22q11.2DS patients with recurrent infections, regardless of their age, which probably contributes to the immunodeficiency in some patients.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, the results obtained from the TREC assay may be used to classify patients based on the status of their immunity, predicting susceptibility to infections. In this study, we found that the TREC levels were significantly lower in individuals with 22q11.2DS compared with healthy controls and tended to decrease with age due to the natural thymic involution, as has been previously shown (6,(22)(23)(24). Furthermore, lower TREC levels were found in 22q11.2DS patients with recurrent infections, regardless of their age, which probably contributes to the immunodeficiency in some patients.…”
Section: Discussionsupporting
confidence: 75%
“…T-cell receptor excision circles (TRECs) and kappadeleting recombination excision circles (KRECs), such as circular DNA segments that persist in T cells and B cells, were recently considered markers of new lymphocyte output [32]. Kamae et al [33] indicated that low TREC and/or KREC levels are useful biomarkers that are associated with the overall survival rate in CVID patients.…”
Section: T-cell Abnormalities In Cvidmentioning
confidence: 99%
“…TRECs and KRECs are circular episomes of DNA that are formed into differentiating T- and B-cell progenitors during V(D)J rearrangement in the thymus and bone marrow. It is supposed that TREC and KREC measurement could be a valuable marker for lymphocyte neogenesis [6]. …”
Section: Introductionmentioning
confidence: 99%